From Liberal Statebuilding to Counterinsurgency and Stabilization: The International Intervention in Iraq. Issue 5 (20th October 2019) - Belloni, Roberto; Costantini, Irene
ABSTRACT: Stabilization approaches have limited transformational ambitions, in particular when compared with previous large-scale peacebuilding interventions. The case of Iraq is illustrative of such an approach. It demonstrates how achieving stability in the country is no longer supposed to be the result of an overall political, economic and social transformation—as postulated in the initial phase of the intervention—but, rather, a precondition to it. This paper first identifies the circumstances under which stabilization emerged in Iraq and then it traces its main characteristics. Second, it discusses the stabilization approach of the two main international military and civilian actors: the Global Coalition against Daesh and the United Nations Development Programme. In conclusion, the paper argues that while stabilization is likely to freeze the conflict, it remains to be seen whether it will be effective in solving it.